Estimativa de energia no infinito para equações hiperbólicas com coeficientes oscilantes - Zapata, Miguel Angel Cuayla (2012)
We study the behavior, as t ∞, of the energy for the solutions of the Cauchy problem for some strictly hyperbolic linear second order equations with coeficients very rapidly oscillating.